Two new species of the deep-sea genus Parameiropsis (Copepoda: Harpacticoida) from the eastern central Pacific - Cho, Dae Hyun; Wi, Jin Hee; Suh, Hae-Lip (Zootaxa, 2016)
Two new species of Parameiropsis are herein described that were identified from the Korean Deep Ocean Study (KODOS) in the Clarion–Clipperton Fracture Zone, located in the eastern central Pacific. Parameiropsis kodosensis n. sp. is similar to P. magnus Itô, 1983 in two key respects: the presence of a distal seta on the syncoxa of the maxilliped, and the general features of its swimming legs. However, P. kodosensis can be differentiated from P. magnus by a higher length-to-width ratio of the caudal ramus (2.5:1 and 1:1 respectively), the setal number on the exp-3 of P1, and the exp and benp of P5 are separated in P. kodosensis, while they are fused in P. magnus. Parameiropsis tetraspinosa n. sp. resembles P. peruanus Becker, 1974 in the absence of a fused seta in the outermost spine on the endopod of antenna and the general features of the swimming legs. However, P. tetraspinosa can be distinguished from P. peruanus by a higher length-to-width ratio of the caudal ramus (3.9:1 and 2.3:1 respectively), the presence of a distal seta on the syncoxa of the maxilliped, and by its medially fused P5. In this study full descriptions and a comparison with previously described species are provided. Additionally, a key to females of Parameiropsis species is given.